Endovascular treatment of cribriform plate dural arteriovenous fistulas: technical difficulties and complications avoidance. (31st August 2015) - Robert, Thomas; Blanc, Raphaël; Smajda, Stanislas; Ciccio, Gabriele; Redjem, Hocine; Bartolini, Bruno; Fahed, Robert; Piotin, Michel
Abstract : Objective: Cribriform plate dural arteriovenous fistula (dAVF) is a rare pathology, for which the treatment of choice used to be neurosurgery. Technological advances in micro-catheters and embolic agents permitted new endovascular alternatives. Methods: We included all patients treated endovascularly for a cribriform plate dAVF between 2008 and 2013. We retrospectively analysed data focusing on the type of treatment chosen. Results: Ten patients were treated by endovascular approach, with a need for an additional surgical exclusion of the fistula in two cases. Thirteen embolisation sessions were done. Embolisation of the fistula through an ethmoidal artery was the technique of choice; the catheterism of the ophthalmic artery was impossible in two cases and the embolic agent did not penetrate in four cases. The embolisation through the middle meningeal artery was successful in one case but the tortuosity of this artery prevented good penetration of the embolic agent. Venous approach was successful in all cases but was limited to fistulas with superficial venous drainage. Conclusions: Endovascular treatment of cribriform plate dAVF is safe and effective. The embolisation through ethmoidal artery is the method of choice. Branches of the middle meningeal artery are tortuous and prevent the penetration of embolic agent. Venous approach is effective but is limited to cases of failure of the arterial approach.